2019
DOI: 10.5005/jp-journals-10025-1180
|View full text |Cite
|
Sign up to set email alerts
|

A Case of True Superior Keratoconus Confirmed Using Multiple Imaging Modalities

Abstract: Aim: To report an unusual case of a newly diagnosed bilateral superior keratoconus in an elderly patient. Background: We report a case of bilateral superior keratoconus in a 64-year-old woman who was diagnosed after having presented with hydrops in one eye. Case description: Uncorrected visual acuity was counting fingers from 3 and 1 meter for the right and left eyes, respectively. A superiorly located deep stromal scar and chronic corneal edema consistent with a diagnosis of corneal hydrops were noted for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(23 reference statements)
0
0
0
Order By: Relevance
“…The diagnosis was supported by Pentacam (OCULUS Optikgeräte GmbH, Wetzlar, Germany) demonstrating corresponding SCS and thinning. Özalp et al 10 reported on bilateral SKC with corneal hydrops in one eye. The diagnosis was confirmed by Pentacam, anterior segment optical coherence tomography, and epithelial thickness map, while the difference in the corneal thicknesses between the central and the superior zones was only 5 µm, the difference in the epithelial thicknesses between the respective zones was 24 µm.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The diagnosis was supported by Pentacam (OCULUS Optikgeräte GmbH, Wetzlar, Germany) demonstrating corresponding SCS and thinning. Özalp et al 10 reported on bilateral SKC with corneal hydrops in one eye. The diagnosis was confirmed by Pentacam, anterior segment optical coherence tomography, and epithelial thickness map, while the difference in the corneal thicknesses between the central and the superior zones was only 5 µm, the difference in the epithelial thicknesses between the respective zones was 24 µm.…”
Section: Literature Reviewmentioning
confidence: 99%